மொழி, இலக்கிய ஆய்வு நெறியியல் - (:unkn) unknown (Central Institute of Indian Languages Mysore, 2015)
This book presents the methodologies that must be adopted during academic research in and about language and literature.
Research Methodologies For Language And Literature
Keywords: Tamil; Research Methodologies For Language And Literature; Research Methodology; Tamil; Tamil